A survey on coronaviruses in bats from São Paulo City - Molina, Cesar Martin Leyva (2024)
Coronaviruses are important pathogens that have caused economic losses on farms and have also led to outbreaks of diseases in humans. These viruses have shown the ability to adapt to a wide variety of animals, making it necessary to know which coronaviruses circulate in wild animals in order to react more quickly to future zoonotic outbreaks. The order Chiroptera consists of an abundance of bat species distributed almost worldwide, capable of serving as reservoirs for different viruses, notably coronaviruses. Brazil harbors a large number of bat species, but studies on viruses in these animals are scarce for such diversity. The original objective of this work was to detect the presence of coronaviruses in bats from São Paulo, but we were also able to evaluate samples from Ceará. Using semi-nested RT-PCR and High Throughput Sequencing, we detected the presence of an alphacoronavirus in a bat of the species Molossus molossus from Ceará, and by using a partial sequence of the nsp12 gene, a clear differentiation was found between this coronavirus and others found in bats from Brazil, compared to the coronavirus species considered by the ICTV. Finally, we provide hypotheses to explain the low percentage of positive samples detected in the present work and in Brazil, and suggest that changes in sampling methodology could help obtain better results.